Community Perceptions and Hospital Selection in Depok: A Comparative Study of RSUD Anugerah Sehat Afiat and Competitors Based on the 5A Framework - Faridah, Iva Nur; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
RSUD Anugerah Sehat Afiat (ASA) Depok faces challenges in enhancing service utilization and competitiveness as a public hospital in the increasingly competitive healthcare environment of eastern Depok City. This study aimed to identify factors influencing community preferences in hospital selection and to determine appropriate positioning strategies for RSUD ASA. A mixed-methods case study design was employed. Quantitative data were collected from 132 respondents aged over 25 years who had visited four hospitals included in the study, using structured questionnaires. Qualitative data were obtained through in-depth interviews with eight key informants representing RSUD ASA management. Data analysis was based on five dimensions: availability, affordability, accessibility, accommodation, and acceptability. The results showed that acceptability was the most dominant factor influencing hospital preference (p-value < 0.001), followed by accessibility (p-value = 0.007) and availability (p-value = 0.026). In contrast, affordability and accommodation were not significantly associated with community preference. Qualitative findings supported these results, indicating that patient trust, hospital reputation, service readiness, and ease of access were perceived as the main determinants of hospital choice. These findings suggest that community preference is driven primarily by perceived service value rather than cost or physical facilities. Therefore, positioning RSUD ASA as the community’s primary hospital should focus on strengthening service quality, trust, accessibility, and hospital image through a value-based strategic approach.